2015
DOI: 10.1002/anie.201411618
|View full text |Cite
|
Sign up to set email alerts
|

trans‐Hydrogenation: Application to a Concise and Scalable Synthesis of Brefeldin A

Abstract: The important biochemical probe molecule brefeldin A (1) has served as an inspirational target in the past, but none of the many routes has actually delivered more than just a few milligrams of product, where documented. The approach described herein is clearly more efficient; it hinges upon the first implementation of ruthenium-catalyzed trans-hydrogenation in natural products total synthesis. Because this unorthodox reaction is selective for the triple bond and does not touch the transannular alkene or the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(58 citation statements)
references
References 90 publications
2
56
0
Order By: Relevance
“…49 In a first foray, this method was applied to the total synthesis of (+)-brefeldin A, a macrolactone originally isolated from Penicillum decumbens (Table 4, Entry 3). 50 meso-Diester 186 served as a convenient starting material, which was desymmetrized on large scale with the help of a pig liver esterase-catalyzed semi-hydrolysis (Scheme 15); subsequent ester reduction and lactonization led to compound 188. Oxidative cleavage of the double bond followed by an The yield refers to overall yield over trans-hydrosilylation/protodesilylation.…”
Section: Trans-hydrogenation In Natural Product Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…49 In a first foray, this method was applied to the total synthesis of (+)-brefeldin A, a macrolactone originally isolated from Penicillum decumbens (Table 4, Entry 3). 50 meso-Diester 186 served as a convenient starting material, which was desymmetrized on large scale with the help of a pig liver esterase-catalyzed semi-hydrolysis (Scheme 15); subsequent ester reduction and lactonization led to compound 188. Oxidative cleavage of the double bond followed by an The yield refers to overall yield over trans-hydrosilylation/protodesilylation.…”
Section: Trans-hydrogenation In Natural Product Synthesismentioning
confidence: 99%
“…The advantage of the method lies in its functional group tolerance which was illustrated by the total synthesis of brefeldin A (see Section 3.1); 50 however, over-reduction and/or isomerization of the newly formed double bond do interfere in certain cases. 49,50 Mechanistic investigations using para-hydrogen induced polarization (PHIP) transfer NMR spectroscopy showed that the productive trans-reduction competes with a pathway in which both H-atoms of H 2 are delivered to a single alkyne C-atom of the substrate, whilst the second alkyne C-atom converts into a metal carbene; a representative case is shown in Scheme 6. 51,52 This unprecedented "geminal-hydrogenation" mode of substrates such as 13 was confirmed by isolation and structural characterization of a pertinent ruthenium carbene complex.…”
Section: Introductionmentioning
confidence: 99%
“…27−31 The observed chemoselectivity for alkyne reduction in the presence of vulnerable functional groups raises the possibility of using this technology for latestage introduction of trans-alkene moieties. 32 While the optimal system utilized the precious metals Ag and Ru, non-precious metal analogues pairing Cu and/or Fe did show some activity and represent opportunities for further development. Understanding the nature of heterobimetallic H 2 activation, the catalytic mechanism, and the selectivity-determining reaction steps will aid in the design of second-generation systems featuring nonprecious metals capable of operating efficiently and selectively under mild conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Of the different hydrometalation reactions investigated, trans ‐hydrostannation proved to be most receptive to this effect . In any case, compounds of type C provide many opportunities for downstream functionalization, as witnessed by a growing number of applications to target‐ and/or diversity‐oriented synthesis …”
Section: Introductionmentioning
confidence: 99%